2020
DOI: 10.1101/2020.06.16.154534
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Controlling protein nanocage assembly with hydrostatic pressure

Abstract: 22Controlling the assembly and disassembly of nanoscale protein cages for the 23 capture and internalisation of protein or non-proteinaceous components is 24 fundamentally important to a diverse range of bionanotechnological 25 applications. Here, we study the reversible, pressure-induced dissociation of a 26 natural protein nanocage, E. coli bacterioferritin (Bfr), using synchrotron 27 radiation small angle X-ray scattering (SAXS) and circular dichroism (CD). We 28 demonstrate that hydrostatic pressures of 45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…For example, by identifying critical interactions between nanocage subunits that may affect the assembly process, future genetic engineering efforts of subunits may lead to enhanced control over conditions that trigger disassembly/ reassembly, size, structure, and cargo-loading efficiency of encapsulins. 50,51 In summary, the findings of this study advance our understanding of encapsulins by providing critical insight into their unique disassembly/reassembly dynamics. This knowledge provides a roadmap toward an encapsulin "tool kit" comprising nanocages with varying structural architectures and biochemical/biophysical properties, which can be readily selected and further customized for a specific nanobiotechnological application.…”
Section: ■ Conclusionmentioning
confidence: 74%
“…For example, by identifying critical interactions between nanocage subunits that may affect the assembly process, future genetic engineering efforts of subunits may lead to enhanced control over conditions that trigger disassembly/ reassembly, size, structure, and cargo-loading efficiency of encapsulins. 50,51 In summary, the findings of this study advance our understanding of encapsulins by providing critical insight into their unique disassembly/reassembly dynamics. This knowledge provides a roadmap toward an encapsulin "tool kit" comprising nanocages with varying structural architectures and biochemical/biophysical properties, which can be readily selected and further customized for a specific nanobiotechnological application.…”
Section: ■ Conclusionmentioning
confidence: 74%
“…41 It was demonstrated that a hydrostatic pressure of 450 MPa is sufficient to completely dissociate the ferritin nanocage into protein dimers, and the reassembly process could be controlled by selecting appropriate buffer conditions. 42…”
Section: Loading Of Small-molecule Drugs Within the Ferritin Nanocagementioning
confidence: 99%
“…Structural alterations in proteins under HHP treatment HHP is known to induce changes in protein folding and oligomerization, and this change primarily occurs by influencing weak bonds, especially those in hydrophobic interactions and electrostatic interactions (Le Vay et al, 2020). Moreover, pressures below 1 GPa rarely break covalent bonds; therefore, the primary structures of proteins are unaffected by HHP (Silva et al, 2014).…”
Section: 1mentioning
confidence: 99%
“…Although protein unfolding may also expose hydrophobic AA residues and consequently increase the hydration volume, the net changes in V Φ upon unfolding are mostly negative (Chen & Makhatadze, 2017). In addition, pressurization favors the dissociation of oligomeric proteins, and this process can be ascribed to the disruption of interfacial protein-protein interactions due to protein unfolding (Le Vay et al, 2020).…”
Section: 1mentioning
confidence: 99%
See 1 more Smart Citation